2013
DOI: 10.1093/nar/gkt1162
|View full text |Cite
|
Sign up to set email alerts
|

Modification of picornavirus genomic RNA using ‘click’ chemistry shows that unlinking of the VPg peptide is dispensable for translation and replication of the incoming viral RNA

Abstract: Picornaviruses constitute a large group of viruses comprising medically and economically important pathogens such as poliovirus, coxsackievirus, rhinovirus, enterovirus 71 and foot-and-mouth disease virus. A unique characteristic of these viruses is the use of a viral peptide (VPg) as primer for viral RNA synthesis. As a consequence, all newly formed viral RNA molecules possess a covalently linked VPg peptide. It is known that VPg is enzymatically released from the incoming viral RNA by a host protein, called … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 40 publications
2
27
0
Order By: Relevance
“…Due to the lack of information or limitation in the experimental designs, there is still a major gap in knowledge for the role of the 5 UTRs of most Potyviridae in translation. The VPg has not been reported to be involved in translation for Picornaviridae (Langereis et al, 2014). Note the atypically long 5 untranslated region of the newly emerged virus of wheat, Triticum mosaic virus (Family Potyviridae, genus Poacevirus) with an atypical higher GC content (42.1%) and G, determined by mFOLD prediction of −205.7 kcal/mol, which would suggest stable secondary structures.…”
Section: Potato Virus a (Pva)mentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the lack of information or limitation in the experimental designs, there is still a major gap in knowledge for the role of the 5 UTRs of most Potyviridae in translation. The VPg has not been reported to be involved in translation for Picornaviridae (Langereis et al, 2014). Note the atypically long 5 untranslated region of the newly emerged virus of wheat, Triticum mosaic virus (Family Potyviridae, genus Poacevirus) with an atypical higher GC content (42.1%) and G, determined by mFOLD prediction of −205.7 kcal/mol, which would suggest stable secondary structures.…”
Section: Potato Virus a (Pva)mentioning
confidence: 99%
“…Moreover, potyviruses differ from picornaviruses in that their VPg proteins are several fold larger (picornaviruses ∼2-3 kDa, potyviruses ∼20-23 kDa) and are presumably involved in translation, or at least interact with the cap-binding factors (Wang and Krishnaswamy, 2012). The VPg seems to be dispensable for animal picornavirus translation (Langereis et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Ideally, these methods should require few steps; are of high efficiency and yield; and use gentle, commercially available, and noncytotoxic materials. Diverse fluorescent labeling methods of endogenous RNAs are available to meet these goals . Many of these methods are plagued by issues relating to limited dye permeability through the cell membrane, nonspecific dye binding, cytotoxicity, necessary modifications to the genome, high‐molecular‐weight RNA extensions, and high intrinsic background; hence, they are often impractical for monitoring low‐abundance and short transcripts .…”
Section: Introductionmentioning
confidence: 99%
“…In EV, VPg remains bound to the 5’ end of the viral RNA 16 , although it may be removed at some phase of replication 56 . Here, we have shown that the previously identified binding site for VPg on the surface of the CVA24 3D pol (Figure 1 & 2) is, indeed, an allosteric site, as compounds selected to bind there interfere with both uridylylation and subsequent elongation to VPgpolyU (Figures 3 & 5).…”
Section: Discussionmentioning
confidence: 99%